Toward bidirectional photoswitchable colored photochromic molecules with visible light stability. Issue 67 (6th August 2018) - Zhan, Tian-Guang; Yin, Huan-Huan; Zheng, Si-Tai; Lin, Wei-Cheng; Shen, Nan-Li; Cui, Jiecheng; Kong, Li-Chun; Liu, Li-Juan; Zhang, Kang-Da
Abstract : Novel bidirectional photoswitchable colored photochromic [2]rotaxanes were fabricated, whose colored states exhibit considerable visible-light stability and high thermal stability. These features are crucial for photochromic molecules to be applied in information displays and data storage. Abstract : Photochromic [2]rotaxanes with bidirectional photoswitchability were fabricated, whose colored states exhibit remarkable visible-light and thermal stabilities as revealed by systematically spectroscopic investigations.